A Low-cost demonstration kit for determination of the active region of x-ray detectors using phototransistors - Saminan, Saminan; Silviana, Fitria; Prayogi, Soni (Universitas Sebelas Maret, 2024)
This research develops a low-cost demonstration kit that aims to facilitate understanding of the concept of determining the active region of an X-ray detector using a phototransistor. This demonstration kit provides a practical and effective tool for illustrating the basic principles of X-ray detection, focusing on the phototransistor as the main component. The research method includes designing an electronic circuit capable of converting changes in light received by a phototransistor into an electrical signal that can be measured. The interaction of X-rays with matter can produce fluorescence phenomena that emit visible light. This phenomenon is utilized to design a phototransistor-based X-ray detector by attaching a ZnS (Ag) fluorescent screen to the surface of a phototransistor arranged in a Darlington circuit. The measurement of the active area of the detector was carried out by collimating the x-ray beam from a 2000-watt Philips x-ray generator tube, 60 kV type PW 2215/20 NR 780026, and measuring the output voltage of the detector (Vout) every 1 mm the change in beam position horizontally or vertically. The experimental results show that the Darlington circuit can be applied to design phototransistor-based X-ray detectors. The detector's active area irradiated with x-rays was obtained at (3.5 ± 0.5) mm horizontally and (3.3 ± 0.5) mm in the vertical direction. The results validate the phototransistor's response to X-rays and provide a clear illustration of how the active region of the detector can be identified and measured.